Correlation between total animal and plant protein intake, with body mass index in tuberculosis patients during the intensive phase in Dili and Oecusse - marques lafo, merita; Chandra, Dian Novita; Nurwidya, Fariz; Sequiera, Ercia Maria da Conceicao (World Nutrition Journal, 2024)
Tuberculosis causes decreased appetite and hypermetabolism, disrupting protein breakdown and synthesis, leading to malnutrition. Proteins, as the primary source of amino acids, support immune cells and help prevent malnutrition and susceptibility to other infections. The intensive phase of tuberculosis therapy is crucial for enhancing immune defense, reducing the bacterial load, and decreasing energy expenditure, thereby increasing body weight.